Answer:
Angle = Ф =
(0) = 0
Hence, it is proved that angle between position vector r and acceleration vector a = 0 and is it never changes.
Explanation:
Given vector r(t) =
![e^(t)cost i + e^(t)sint j](https://img.qammunity.org/2022/formulas/mathematics/high-school/dbvetis7wtn7i62pjjsxpvloj92vvxol0o.png)
As we know that,
velocity vector = v =
![(dr)/(dt)](https://img.qammunity.org/2022/formulas/mathematics/high-school/hnzou3v0y1qryukbrpd5w9j87v3omp60ai.png)
Implies that
velocity vector =
![(e^(t) cost - e^(t) sint)i + (e^(t) sint - e^(t)cost )j](https://img.qammunity.org/2022/formulas/mathematics/high-school/q32w4kreow9yrlkch5g6df2oo1brn2r5zx.png)
As acceleration is velocity over time so:
acceleration vector = a =
![(dv)/(dt)](https://img.qammunity.org/2022/formulas/mathematics/high-school/4aydjtv6473zoz38ufivxi98mzjrs5g137.png)
Implies that
vector a =
![(e^(t)cost - e^(t)sint - e^(t)sint - e^(t)cost )i + ( e^(t)sint + e^(t)cost + e^(t)cost - e^(t)sint )j](https://img.qammunity.org/2022/formulas/mathematics/high-school/fgvsa2kekt3c61yd2r4nlj8jrvwtvh7r7w.png)
vector a =
![(-2e^(t)sint) i + ( 2e^(t)cost)j](https://img.qammunity.org/2022/formulas/mathematics/high-school/9u72eei58pjqzolguh19hcbg4zq11ofw0p.png)
Now scalar product of position vector r and acceleration vector a:
r. a =
![<e^(t)cost, e^(t)sint> . <-2e^(t)sint, 2e^(t)cost>\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/bl7t9l3y1ybbkkjg7fm5ecu4imbs5xg4s4.png)
r.a =
![-2e^(2t)sintcost + 2e^(2t)sintcost](https://img.qammunity.org/2022/formulas/mathematics/high-school/62ao9k8ronxug549jid374ix9dtngu3wid.png)
r.a = 0
Now, for angle between position vector r and acceleration vector a is given by:
cosФ =
=
![(0)/(|r|.|a|) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/yhpni8x7f2fxflypbp1vegml052f8dkh7l.png)
Ф =
(0) = 0
Hence, it is proved that angle between position vector r and acceleration vector a = 0 and is it never changes.